Phase I Study of Docetaxel and Temsirolimus in Refractory Solid Tumors. (September 2021) - Amin, Manik; Gao, Feng; Terrero, Gretel; Picus, Joel; Wang-Gillam, Andrea; Suresh, Rama; Ma, Cynthia; Tan, Benjamin; Baggstrom, Maria; Naughton, Michael J.; Trull, Lauren; Belanger, Stephanie; et al.
Abstract : Introduction: The mammalian target of rapamycin (mTOR) is a downstream mediator in the phosphatidylinositol 3-kinase/Akt signaling pathway, and plays a central role in cell proliferation, growth, differentiation, migration, and survival. Temsirolimus (CCI-779), a selective inhibitor of the mTOR, is an ester analog of rapamycin (sirolimus) with improved aqueous solubility and pharmacokinetic (PK) properties. Preclinical studies have confirmed additive and synergistic antitumor activity in cancer cell lines (breast, prostate cancer) with combinations of taxanes and mTOR inhibitors. We conducted a phase I open-label, dose-escalation study to determine the maximal tolerated dose (MTD) of docetaxel in combination with temsirolimus in patients with refractory solid tumors. Patients and Methods: Eligible patients had a diagnosis of a refractory solid malignancy, measurable disease, and adequate organ function. Patients were sequentially enrolled in 4 dose level intravenous combinations of docetaxel and temsirolimus. Temsirolimus was administered weekly with docetaxel administered every 3 weeks. Laboratory data for tumor markers and radiologic imaging were conducted prestudy and then after every 2 cycles of the treatment. Radiologic response was assessed by Response Evaluation Criteria in Solid Tumors (RECIST) criteria. Blood samples for PK and pharmacodynamic analysis were planned to be drawn at MTD. Apart from the traditional 3+3 design, we also implemented Bayesian Optimal Interval design which uses isotonic regression method to select MTD. We proceeded with isotonic regression analysis by using 20% dose-limiting toxicity (DLT) rate as target. Results: Twenty-six patients were treated in this study in 4 cohorts and dose levels. Fourteen males and 12 females were enrolled with a median age of 50 years (range of 27 to 72 y) and median Eastern Cooperative Oncology Group performance score of 1. Tumor histologies included pancreas (6), colon (5), rectum (3), gallbladder (2), non–small cell lung (2), endometrium (1), neuroendocrine (1), esophagus (1), stomach (1), pharynx (1), small intestine (1), and duodenum (1). Stable disease was observed in 2/4 (50%), 3/7 (43%), 4/10 (40%), and 3/5 (60%) patients in cohorts 1, 2, 3, and 4, respectively. Dose escalation in cohorts 2, 3, and 4 was complicated by DLTs such as grade 4 neutropenia and grade 3 diarrhea and an inability for patients to tolerate treatments during and beyond cycle 1 without dose reductions. Therefore, we could not determine an MTD or recommended phase II dose using the traditional 3+3 study analysis. Blood samples for PK and pharmacodynamic analysis were not collected since MTD was not determined. By using 20% DLT rate closest to the target, isotonic regression analysis showed identical estimated DLT rates in dose −1 (docetaxel 50 mg/m 2 and temsirolimus 15 mg/m 2 ) and dose level 1 (docetaxel 60mg/m 2 and temsirolimus 15 mg/m 2 ). Conclusions: Dose escalation of docetaxel and temsirolimus was limited by severe myelosuppressive toxicity in this phase I study. Most of the DLTs occurred after cycle 1 of therapy hence, we were unable to determine MTD or collect blood samples for PK and pharmacodynamic analysis. Our trial did not meet its objectives due to significant DLTs with this chemotherapy combination. Although our novel use of Bayesian Optimal Interval design using isotonic regression method to select MTD showed identical estimated DLT rates in dose levels 1 and −1, clinically our patients were not able to complete 2 cycles of this regimen without dose reductions due to myelosuppressive toxicity in either of these dose levels, and hence, escaped clinical validity. This combination regimen should not be studied further at the dose levels and schedules tested in our study.